Roh Kudus dan Tata Kelola Gereja: (Rekonstruksi Pneumatologis atas Transparansi Finansial Neo-Pentakosta di Indonesia) - Stefanus De Fatima Nahac (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2026)
Public demand for transparency from religious organizations has continued to rise in recent years, requiring church finances to be subject to both public regulatory oversight and internal accountability mechanisms. This study examines Indonesia’s neo-Pentecostal churches as its research object and employs a conceptual analysis approach to establish a critical dialogue between theological perspectives and contemporary governance literature. The study explores how theological claims influence financial decision-making processes and identifies three categories of theological claims that may limit external scrutiny and accountability. Furthermore, the findings reveal that four categories of theological claims have the potential to legitimize excessive authority among church leaders, thereby weakening three essential oversight mechanisms. Based on these findings, this research proposes a reconstructed pneumatological governance model that integrates spiritual leadership with transparent and accountable financial practices. The study argues that financial transparency is not merely an administrative requirement but a fundamental expression of ecclesiastical integrity that reflects the authenticity of a church’s claim to be guided by the Holy Spirit.